Nonsteroidal anti‐inflammatory drug associations with nonmelanoma skin cancer – the saga continues. (1st October 2019) - Rundle, C.W.; Dellavalle, R.P.
Abstract: Linked Article: Pandeya et al. Br J Dermatol 2019; 181 :749–760 .